Carriage of Distinct mcr‐1‐Harboring Plasmids by Unusual Serotypes of Salmonella. Issue 3 (11th February 2020) - Tang, Biao; Chang, Jiang; Zhang, Ling; Liu, Lizhang; Xia, Xiaodong; Hassan, Bachar H.; Jia, Xu; Yang, Hua; Feng, Youjun
Abstract: Colistin acts as a last‐resort antibiotic against lethal infections by carbapenem‐resistant Enterobacterial pathogens. Enterobacteriaceae carrying mobile colistin resistance (MCR) genes are rapidly emerging and threatening human health and food safety. Despite mcr‐1 being prevalent in Escherichia coli, its dissemination in Salmonella is not well characterized. Herein, two unusual serotypes of colistin‐resistant Salmonella isolates are reported first, namely serotype Ngor (ST5399) and Goldcoast (ST2529). Using whole genome sequencing, it is shown that mcr‐1 is located on the IncHI2‐like plasmid pTB501 (188, 527 bp) of strain SSDFZ54 and the IncX4‐type plasmid pTB602 (33, 303 bp) in strain SSDFZ69, respectively. Furthermore, the backbone, tra ‐ and antimicrobial resistance genes relative variable regions in the mcr‐1 ‐bearing IncHI2 plasmids are systematically characterized. Phylogenetic analysis shows that all IncHI2‐type plasmids from non‐Chinese regions are clustered together, suggesting a possible Chinese origin. Taken together, these findings extend the understanding of Salmonella as a vehicle of mcr‐1 carriage and distribution. Abstract : This study describes that transferable colistin resistance emerges in two unusual serotypes of Salmonella, namely Ngor (ST5399) and Goldcoast (ST2529). Genome sequencing reveals that two distinct plasmids (IncHI2 and IncX4) acts as vehicles to disseminate mcr‐1 gene, producing phenotypic resistance.